Five channel WDM communication using a single a:SiC-H double pin photo device - Vaz da Silva, V (2016)
Amorphous SiC heterostructures built as a double pin device has a non linear spectral gain which is a function of the signal wavelength that impinges on its front or back surface. Illuminating the device with several single wavelength data channels in the visible spectrum allows for Wavelength Division Multiplexing (WDM) digital communication. Using fixed ultra-violet illumination at the front or back surfaces enables the recovery of the multiplexed channels. Five channels, each using a single wavelength which is modulated by a Manchester coded signal at 12,000 bps, form a frame with 1024 bits with a preamble for signal intensity and synchronisation purposes. Results show that the clustering of the received signal enables the successful recovery of the five channel data using the front and back illumination of the surfaces of the double pin photo device. (C) 2015 Elsevier B.V. All rights reserved.